Providing Social and Educational Services to Young People under the Conditions of Khmelnytskyi Regional Centre of Social Services for Family, Children and Youth - Liudmyla Yakubova (Pedagogical Discourse, 2014)
This article describes and analyzes the provision of social and educational services by the staff of social services for family, children and youth. We have described the information relating the activity of Khmelnytsky Regional Centre of Social Services for Family, Children and Youth, which concerns the organization of social services for youth. We considered the question as for the the principles and accounting of provision of social services, the order of social services offering, categories of beneficiaries and glossary of problems, among which we have selected those that relate to young people, young families etc.